Postcategorical utopia : James Baldwin and the political unconscious of imagined futures - Kilpeläinen, Pekka, 1971- (Oxford ; New York : Peter Lang, 2023)
"This book examines the dialectic of ideology and utopia in three novels by James Baldwin. Taking Fredric Jameson's seminal theory of the political unconscious as its point of departure, Dr Pekka Kilpeläinen conceptualizes Baldwin's writing in terms of the impulse of postcategorical utopia, where the ideological categorizations based on race and sexuality, in particular, are challenged by the utopian impulse to imagine alternative futures. The readings of three of Baldwin's novels probe into the questions of ideological and utopian spatialities, transgressive interracial and same-sex relationships, and critiques of both Western modernity and its black counterculture. Baldwin's denouncement of the oppressive effects of identity categories penetrates his entire oeuvre, from his early, critically acclaimed work to his later, often ignored novels. Seen through the lens of postcategorical utopia, the urgency of Baldwin's vision gains a new sense of immediacy and relevance"--
Introduction: James Baldwin and the Utopian Impulse -- Reading Politically: Fredric Jameson, Ideology and Utopia -- Geographies of Ideology and Utopia in Go Tell It on the Mountain -- Black Christ(opher) and the Triangle of Postcategorical Love in Tell Me How Long the Train’s Been Gone -- Beyond Modernity and Its Black Counterculture: The Dialectic of Ideology and Utopia in Just Above My Head -- Conclusion: Postcategorical Utopia and Messianic Time.
Vertaisarvioitu.
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: Baldwin, James, -- 1924-1987 -- Criticism and interpretation; Utopias in literature; Ideology in literature; kirjallisuudentutkimus; englanninkielinen kirjallisuus; utopiat; ideologiat; afroamerikkalainen kirjallisuus; rotupolitiikka; sukupuolisyrjintä; litteraturvetenskap; litteratur på engelska; utopier; ideologier; afroamerikansk litteratur; raspolitik; könsdiskriminering